Insights into formation, detection and removal of the beany flavor in soybean protein. (June 2021) - Wang, Bei; Zhang, Qiang; Zhang, Na; Bak, Kathrine H.; Soladoye, Olugbenga P.; Aluko, Rotimi E.; Fu, Yu; Zhang, Yuhao
Abstract: Background: Plant-based meat analogues (PBMA) are promising to address the issue of imbalance between global meat supply and demand. PBMA can contribute to an environmentally friendly and sustainable food production. As one of the main raw materials in PBMA, the naturally occurring beany flavor in soybean restricts their further development and consumer acceptance. To enhance the application of soybean as an ingredient in PBMA as well as improve consumer acceptability, the beany flavor should be effectively eliminated. Scope and approach: In the present review, the main beany flavor compounds, their formation mechanism, the interaction between soybean protein and off-flavor compounds, the detection methods, and the removal methods were systematically reviewed. Notably, the main removal approaches for beany flavor of soybean can be divided into three categories, namely biotechnological, physical and chemical methods. The different removal methods of beany flavor in soybean protein were compared and discussed. Key findings and conclusions: Application of biotechnological methods to eliminate beany flavor in soybean is challenging. Although enzymatic method is safe and clean, its catalytic efficiency is relatively low. Chemical modification methods possess food safety threats. By contrast, physical processing is relatively effective in removing beany flavor, while heating may exert a negative impact on the functional properties of soybean protein. Collectively, enzymatic modification combined with novel non-thermal processing as well as the optimized texturization process of soybean protein is of great significance to elimination of beany flavor in PBMA. Graphical abstract: Image 1 Highlights: Over 20 low-threshold volatile compounds account for beany flavor, and their formation mechanisms were described. The detection methods of beany flavor compounds in soybean were reviewed. The main removal methods for beany flavor include biotechnological, physical, and chemical methods. The non-thermal processing technology and enzymatic modification are promising to removal of beany flavor. This review provides a theoretical reference for removal of beany flavor in plant-based meat analogues.